If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 1)(9n + 8) = 0 Reorder the terms: (1 + n)(9n + 8) = 0 Reorder the terms: (1 + n)(8 + 9n) = 0 Multiply (1 + n) * (8 + 9n) (1(8 + 9n) + n(8 + 9n)) = 0 ((8 * 1 + 9n * 1) + n(8 + 9n)) = 0 ((8 + 9n) + n(8 + 9n)) = 0 (8 + 9n + (8 * n + 9n * n)) = 0 (8 + 9n + (8n + 9n2)) = 0 Combine like terms: 9n + 8n = 17n (8 + 17n + 9n2) = 0 Solving 8 + 17n + 9n2 = 0 Solving for variable 'n'. Factor a trinomial. (1 + n)(8 + 9n) = 0Subproblem 1
Set the factor '(1 + n)' equal to zero and attempt to solve: Simplifying 1 + n = 0 Solving 1 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + n = 0 + -1 n = 0 + -1 Combine like terms: 0 + -1 = -1 n = -1 Simplifying n = -1Subproblem 2
Set the factor '(8 + 9n)' equal to zero and attempt to solve: Simplifying 8 + 9n = 0 Solving 8 + 9n = 0 Move all terms containing n to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 9n = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 9n = 0 + -8 9n = 0 + -8 Combine like terms: 0 + -8 = -8 9n = -8 Divide each side by '9'. n = -0.8888888889 Simplifying n = -0.8888888889Solution
n = {-1, -0.8888888889}
| 11x-x=42 | | (8x-18)+(x)=90 | | 2/3.3/4=5X | | (q+8)(4q-5)=0 | | 2r^2+8r-3=-11 | | -u+63=249 | | 3x-3(-6)=9 | | 8r^2+8r-3=-11 | | 222=10-y | | 3x-3(0)=9 | | 0=93.5-78x+15x^2 | | 104=170-v | | (13x-2)+(x)=90 | | x*y=575000 | | 4v-7=-19 | | Y=0.3x+35 | | 7/3=6/x | | 0=1-2x+4x^2 | | 2826=2r*3.14 | | X-78=1/3×x-82 | | -6=m/5-3 | | 3(x+1)-2x=5-3x | | (4xb)-8=8 | | 2(t+7)=48 | | 9+3r-1=8r+16-3r | | 7n-1=169 | | 16x^2-2x-8=21 | | 3/7(x-8)=-3 | | 85-5x=15 | | -2(x-8)=10 | | 16x^2-2x-8=0 | | 3/7(x-8)=3 |